Statins for major depressive disorder: A systematic review and meta-analysis of randomized controlled trials. - Riccardo De Giorgi; Franco De Crescenzo; Nicola Rizzo Pesci; Marieke Martens; Wendy Howard; Philip J Cowen; Catherine J Harmer (PLoS ONE)
Background The burden of depressive disorder is large and new treatment approaches are required. Repurposing widely available drugs such as statins may be a time- and cost-effective solution. Statins have anti-inflammatory and anti-oxidant properties which have been shown to be relevant to the pathophysiology of depression. This study assesses the efficacy, acceptability, tolerability, and safety of statins in major depressive disorder. Methods Our study is an update and extension of a previous meta-analysis published in 2016 by Salagre et al. We performed a systematic review (PubMed/MEDLINE, Cochrane CENTRAL, ISI Web of Science, CINAHL, and ClinicalTrials.gov until the 1st September 2020) and meta-analysis of randomized controlled trials using any statin against placebo or any other statin in the treatment of major depressive disorder. Our primary efficacy outcome measure was the mean value on any standardized scale for depressive symptoms at 8 weeks of treatment. We also calculated outcomes for efficacy, response, and remission at 2, 4, and 12 weeks, as well as acceptability (dropouts for any cause), tolerability (dropouts due to any adverse event), and safety (any adverse event) outcomes at the studies' endpoints. Furthermore, we conducted an exploratory network meta-analysis for the primary efficacy outcome to identify potential differences between statins. Results We retrieved five randomized controlled trials meeting our inclusion criteria: four used a statin in addition to an antidepressant and compared it to placebo plus antidepressant, and one compared two statins alone. and one comparing one statin with another. Statins compared to placebo in addition to antidepressants were efficacious at 8 weeks (N = 255, SMD = -0.48, 95% CI = -0.74 to -0. 22) and 12 weeks (N = 134, SMD = -0.47, 95% CI = -0.89 to -0.05, moderate certainty) with no difference for acceptability, tolerability, and safety (low certainty). An exploratory network meta-analysis suggested that the most lipophilic statins, especially simvastatin, could be more efficacious than less lipophilic or hydrophilic molecules. Conclusions This systematic review suggests the efficacy, acceptability, tolerability, and safety of statins in addition to antidepressants in patients with major depressive disorder. Further clinical trials in different settings are required to test this result. Trial rgistration PROSPERO registration: CRD42020170938.